Commercial fish ELISA kits have a limited capacity to detect different fish species and their products. (15th June 2020) - Ruethers, Thimo; Taki, Aya C; Khangurha, Jasmit; Roberts, James; Buddhadasa, Saman; Clarke, Dean; Hedges, Claire E; Campbell, Dianne E; Kamath, Sandip D; Lopata, Andreas L; Koeberl, Martina
Abstract: BACKGROUND: Fish is a major food and allergen source, requiring safety declarations on packages. Enzyme‐linked immunosorbent assays (ELISAs) are often used to ensure that the product meets the required standards with regard to the presence of allergens. Over 1000 different fish species are traded and consumed worldwide, and they are increasingly provided by aquaculture. Up to 3% of the general population is at risk of sometimes fatal allergic reactions to fish, requiring strict avoidance of this commodity. The aim of this study is to evaluate the capacity of three commercially available ELISA tests to detect a wide variety of bony and cartilaginous fish and their products, which is essential to ensure reliable and safe food labeling. RESULTS: The detection rates for 57 bony fish ranged from 26% to 61%. Common European and North American species, including carp, cod, and salmon species, demonstrated a higher detection rate than those from the Asia‐Pacific region, including pangasius and several mackerel and tuna species. Among the 17 canned bony fish products, only 65% to 86% were detected, with tuna showing the lowest rate. None of the cartilaginous fish ( n = 9), other vertebrates ( n = 8), or shellfish ( n = 5) were detected. CONCLUSIONS: We demonstrated that three commercial fish ELISA kits had a limited capacity to detect fish and their products. The complexity of fish as a protein source that is increasingly utilized means that there is an urgent need for improved detection methods. This is crucial for the food industry to provide safe seafood products and comply with international legislation. © 2020 Society of Chemical Industry